Digital Representation of Analog Signals by Timed Sequences of Events - Bilinskis, I.; Sudars, K. (Elektronika ir Elektrotechnika, 2008)
A specific signal digitising technique, based on signal sample value taking at time instants when the signal crosses a sinusoidal reference function, is considered. The various digital representations of the original signals obtained in this way have invariable envelope and that leads to specific features of the digital signals unparalleled by other digital signals. The timed sampling event sequences then actually could be considered as digital signals fully representing the respective original analog signals in the digital domain. Adding these signals to the collection of other more conventional digital signal types widen the application range for digital signal processing and provides for specific application options. Ill. 6, bibl. 3 (in English; summaries in English, Russian and Lithuanian).